Hybrid Software Development with Scrum: Perceptions of Brazilian Software Practitioners - Feitosa, Tânia Maria; Machado, Ivan; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
Software processes are crucial in software development projects, affecting product quality and developer team productivity. Agile and plan-oriented approaches can be used in the same project, leading to hybrid software development approaches.Some studies propose hybrid strategies or attempt to characterize and identify related practices. As cultural and organizational factors may impact hybrid process adoption and enactment this paper presents a survey conducted in the Brazilian software industry to investigate various aspects of software process hybridization, using Scrum as a base. Scrum is a flexible and frequently customized agile approach, offering several software process hybridization possibilities. We collected responses from 76 participants across different states in Brazil, and our findings reveal that definitions of software process hybridization differ between industry and literature. Furthermore, we found that several hybridization alternatives are being employed to meet deadlines, manage software complexity, and satisfy customers needs, among other reasons. By sharing our findings, we hope to contribute to the field by establishing a common understanding of software hybridization goals and challenges, ultimately leading to a shared understanding of the benefits of its application, helping Brazilian companies’ productivity.